A new species of Mesocapparis (Capparaceae) from the Brazilian Cerrado - Luber, Jaquelini; Tavares Carrijo, Tatiana; de Freitas Mansano, Vidal (Phytotaxa, 2024)
Mesocapparis minutiflora, a new species for the Cerrado, is described and compared with related species. The taxon is described from the state of Tocantins and Piauí, with only five known collections. It is distinguished from other species mainly by the different shapes of leaf base, petiolar insertion, and the shorter size of petals, gynophore, and filaments. The conservation status of the new species is discussed, and information is provided on its flowering period and geographic distribution.